Method for testing gram volume loss of failed lithium battery negative electrode material

By decomposing and processing the negative electrode material of failed lithium batteries, the proportion of gram capacity loss caused by each influencing factor is calculated, and the problem of difficulty in decomposing influencing factors in the existing technology is solved, and more accurate test results and targeted optimization guidance are achieved.

CN119556158APending Publication Date: 2025-03-04安徽得壹能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771746.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to decompose and determine the severity of each influencing factor that leads to a reduction in the capacity of the negative electrode material of the failed lithium battery, and it is impossible to effectively obtain the loss proportion caused by different influencing factors, making it difficult to provide more targeted guidance on the structural optimization of the negative electrode material.

Method used

By disassembling and removing the negative electrode sheet after discharging the failed lithium battery to a space-electric state, cleaning and dividing it into two parts, and performing different treatments to remove the by-products of the negative electrode particles and the gram capacity loss caused by the crushing of the negative electrode particles. The proportion of gram capacity loss caused by each influencing factor is calculated.

Benefits of technology

The severity of the surface by-products of the negative electrode material and the negative electrode material crushing is clarified, and the direction is pointed out for subsequent improvement of lithium battery failure problems or improving the performance of the negative electrode material, which improves the accuracy and pertinence of the test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119556158A_ABST
    Figure CN119556158A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing gram volume loss of a negative electrode material of a failed lithium battery, and relates to the technical field of lithium ion batteries, and the method comprises the following steps: disassembling the failed lithium battery, taking out a negative electrode plate, cleaning and drying, and dividing into two parts; wiping the dressing on one surface of the first part of negative plate, stamping through a mold, assembling into a button battery, and testing to obtain the gram volume of the invalid negative electrode material; scraping a dressing on one side of a second negative plate to obtain powder, heating and roasting the powder, adding the roasted powder into an acid solution, stirring, mixing the filtered and dried material powder with a conductive material to obtain slurry, coating, cutting, assembling into a button battery, and testing to obtain the gram volume of the cleaned invalid negative plate material; based on the gram volume obtained by testing and the gram volume of the fresh negative electrode material, the proportion of the gram volume loss of the negative electrode material caused by each influence factor is calculated, so that the severity of the surface by-product of the negative electrode material and the severity of the crushing of the negative electrode material can be determined, and a direction is indicated for subsequently improving the failure problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for testing the gram capacity loss of a negative electrode material of a failed lithium battery. Background Art

[0002] In recent years, with the vigorous development of electric vehicles and energy storage power stations, the scale of the lithium-ion battery industry has become larger and larger. In the use or development of lithium-ion batteries, various failure problems often occur, such as low battery capacity, rapid battery cycle capacity decay, battery swelling, large battery pressure difference, etc. Failure analysis of failed lithium batteries can help the battery determine the specific cause of performance degradation and improve and optimize the battery design, thereby improving the reliability of lithium batteries. Among the components of lithium batteries, the gram capacity of positive and negative electrode materials will significantly affect the battery capacity, cycle performance, etc., so it is very important to study and accurately detect the changes in the gram capacity of positive and negative materials in failed lithium batteries.

[0003] The existing method for testing the gram capacity of the negative electrode of an invalid lithium battery, such as patent CN113777491A, usually uses an organic solvent or water to wipe off the dressing on one side of the disassembled negative electrode sheet, and then cuts the wiped electrode sheet into small discs, assembles them into button batteries (referred to as button batteries) for lithium sheets, and obtains the gram capacity of the negative electrode material through charge and discharge tests. On this basis, the loss of gram capacity of the negative electrode material can be determined. However, the above method can only measure the overall gram capacity loss of the negative electrode material, and cannot decompose and determine the severity of the various influencing factors that cause the reduction in the gram capacity of the negative electrode material of the invalid lithium battery, and cannot effectively obtain the loss ratio caused by different influencing factors, and thus it is difficult to provide more targeted guidance on the optimization of the structure of the negative electrode material. Summary of the invention

[0004] In order to address the deficiencies of the above-mentioned prior art, the present invention provides a method for testing the gram capacity loss of failed lithium battery negative electrode materials, taking into account the influencing factors that lead to the reduction of the gram capacity of failed lithium battery negative electrode materials: by-products on the surface of negative electrode particles and breakage of negative electrode materials. By decomposing and calculating the proportion of gram capacity loss caused by different influencing factors, the severity of the by-products on the surface of negative electrode materials and the breakage of negative electrode materials are clarified, which points out the direction for subsequent improvement of lithium battery failure problems or improvement of negative electrode material performance.

[0005] The invention provides a method for testing the gram capacity loss of a negative electrode material of a failed lithium battery.

[0006] A method for testing the gram capacity loss of a failed lithium battery negative electrode material, comprising:

[0007] After discharging the failed lithium battery to an empty state, disassemble and remove the negative electrode sheet, clean the surface of the negative electrode sheet, dry it, and divide it into two parts;

[0008] The dressing on one side of the first negative electrode sheet is wiped off, and the negative electrode sheet is assembled into a button cell after being stamped by a mold, and the gram capacity of the failed negative electrode material is obtained through a small current charge and discharge test;

[0009] The dressing on one side of the second negative electrode sheet is scraped into powder, the powder is heated and calcined and then added to the acid solution, filtered and dried after reaction, the dried material powder is mixed with the conductive material to form a slurry, coated and cut and assembled into a button battery, and subjected to a small current charge and discharge test to obtain the gram capacity of the failed negative electrode material after cleaning;

[0010] Based on the gram capacity obtained from the test and the gram capacity of the non-failed lithium battery negative electrode material, the proportion of gram capacity loss of the negative electrode material caused by various influencing factors is calculated.

[0011] By the above method, the dressing powder scraped from the negative electrode sheet is heated and calcined to remove organic by-products on the surface of the negative electrode particles, and then the calcined powder is added to the acid solution and stirred, filtered and dried to remove inorganic by-products on the negative electrode surface. By the above method, the organic and inorganic by-products on the surface of the negative electrode particles on the negative electrode sheet can be effectively removed, and the gram capacity loss caused by the by-products on the surface of the negative electrode particles and the gram capacity loss caused by the breakage of the negative electrode particles can be accurately detected, which is convenient for subsequent data analysis and processing and lithium battery performance improvement.

[0012] According to a further technical solution, factors affecting the loss of gram capacity of negative electrode materials include byproducts on the surface of negative electrode particles and breakage of negative electrode particles;

[0013] Based on the gram capacity Q1 of the failed negative electrode material and the gram capacity Q2 of the failed negative electrode material after cleaning, combined with the gram capacity Q0 of the non-failed lithium battery negative electrode material, it is calculated that the gram capacity loss of the failed negative electrode material is Q0-Q1, the gram capacity loss caused by by-products on the surface of the negative electrode material is Q2-Q1, and the gram capacity loss caused by breakage of the negative electrode material is Q0-Q2. Furthermore, it is calculated that the proportion of gram capacity loss caused by by-products on the surface of the negative electrode material is (Q2-Q1) / (Q0-Q1), and the proportion of gram capacity loss caused by breakage of the negative electrode material is (Q0-Q2) / (Q0-Q1).

[0014] According to a further technical solution, the byproducts on the surface of the negative electrode particles include organic byproducts on the surface of the negative electrode particles and inorganic byproducts on the surface of the negative electrode particles, wherein the organic byproducts on the surface of the negative electrode particles include alkyl lithium carbonate; the inorganic byproducts on the surface of the negative electrode include lithium carbonate, lithium oxide, and lithium fluoride.

[0015] Further technical solutions, according to the proportion of the negative electrode material gram capacity loss caused by each influencing factor, determine the severity of different influencing factors, and improve the performance of lithium battery negative electrode materials according to the severity, including:

[0016] Compare the percentage of gram capacity loss of failed lithium battery negative electrode materials caused by by-products on the surface of negative electrode particles and that caused by breakage of negative electrode particles. When the percentage of gram capacity loss caused by by-products on the surface of negative electrode particles is larger, the stability of the SEI film on the surface of the negative electrode material is improved; conversely, when the percentage of gram capacity loss caused by breakage of negative electrode particles is larger, the stability of the structure of the negative electrode material itself is improved.

[0017] Through the above method, the proportion of gram capacity loss caused by different influencing factors can be decomposed and calculated, and the severity of the by-products on the surface of the negative electrode material and the breakage of the negative electrode material can be clarified, which can point out the direction for subsequent improvement of lithium battery failure problems or improvement of negative electrode material performance.

[0018] A further technical solution is to disassemble and remove the negative electrode sheet in a glove box or a low-humidity disassembly room, soak and clean the surface of the negative electrode sheet with 500 mL of dimethyl carbonate reagent for 4 hours, and then bake it in a vacuum drying oven at 80°C for 8 hours.

[0019] Through the above method, the disassembled negative electrode sheet can be cleaned with a carbonate solvent and dried after cleaning. The dried negative electrode sheet can be divided into two parts for standby use, so as to clean the lithium salt and electrolyte on the surface of the electrode sheet, avoid the influence of other substances on the gram capacity loss detection, and improve the detection accuracy.

[0020] A further technical solution is to use N,N-dimethylamide organic solvent to wipe off the dressing on one side of the first negative electrode sheet, and then punch the negative electrode sheet after the dressing is wiped off into small discs through a mold, and then assemble them into button batteries for lithium sheets, and use a small current of 0.05C to perform charge and discharge tests on the button batteries. The test voltage range is 0.05mV~2V, and the gram capacity of the failed negative electrode material is obtained through testing Q1.

[0021] A further technical solution is to place the scraped powder into a Ma Furnace and heat it to 400°C for roasting, keep it warm for 4 hours, cool it to room temperature and then place it into a dryer.

[0022] A further technical solution is to add the powder in the dryer to 1 mol L-1 dilute hydrochloric acid or dilute sulfuric acid solution and stir for 8 hours, wash and filter the solid matter with ultrapure water, and place the washed solid matter in a vacuum drying oven and bake at 80°C for 12 hours to obtain material powder.

[0023] A further technical solution is to mix the dried material powder with a conductive material into a slurry, apply it into a pole piece and cut it into small discs, and then assemble it with a lithium sheet into a button battery. The button battery is charged and discharged using a small current of 0.05C. The test voltage range is 0.05mV to 2V. The gram capacity of the failed negative electrode material after cleaning is obtained by testing Q2.

[0024] In a further technical solution, the conductive material includes conductive carbon black, SBR, and CMC;

[0025] Take 1 g of the dried material powder, mix it with conductive carbon black, SBR and CMC in a mass ratio of 95:1.5:2:1.5, and stir to obtain a slurry.

[0026] A further technical solution is to use a vacuum coater to coat the slurry on the copper foil, and then put it into a vacuum drying oven for drying to obtain a machine sheet; wherein the baking temperature is 95°C and the baking time is 8 hours.

[0027] One or more of the above technical solutions have the following beneficial effects:

[0028] 1. The present invention provides a method for testing the gram capacity loss of negative electrode materials of failed lithium batteries, taking into account the influencing factors that lead to the reduction of the gram capacity of negative electrode materials of failed lithium batteries: by-products on the surface of negative electrode particles and breakage of negative electrode materials. For different failed lithium batteries, after processing the negative electrode materials, the gram capacity loss ratio caused by different influencing factors is decomposed and calculated, thereby clarifying the severity of the by-products on the surface of the negative electrode materials and the breakage of the negative electrode materials, and indicating the direction for subsequent improvement of lithium battery failure problems or improvement of negative electrode material performance.

[0029] 2. The testing method proposed in the present invention has a simple operation process, and the accuracy of the detection process is greatly guaranteed by sequentially cleaning and removing organic and inorganic by-products on the surface of the negative electrode particles, which can effectively improve the accuracy of the gram capacity loss test. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0031] Figure 1 A flow chart of the method for testing the gram capacity loss of failed lithium battery negative electrode materials proposed by the present invention;

[0032] Figure 2 This is a schematic diagram of the negative electrode charge and discharge curve of Example 1 of the present invention;

[0033] Figure 3 This is a schematic diagram of the negative electrode charge-discharge curve of Comparative Example 1 of the present invention;

[0034] Figure 4 This is a schematic diagram of the negative electrode charge-discharge curve of Comparative Example 2 of the present invention;

[0035] Figure 5 It is a schematic diagram of the negative electrode charge and discharge curve of comparative example 3 of the present invention. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are exemplary only, are intended to describe specific embodiments, are intended to provide further explanation of the present invention, and are not intended to limit exemplary embodiments according to the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. In addition, it should also be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0037] Considering that a large number of black spots often appear on the surface of the negative electrode sheet during the disassembly of failed lithium batteries, this is because the negative electrode high-activity material not only breaks into materials, but also chemical side reactions occur on the negative electrode surface with the electrolyte components, generating various organic and inorganic byproduct components, covering the surface of the negative electrode particles, resulting in the inability of lithium ions to be normally deintercalated, and the byproducts on the surface of the negative electrode particles, the crushing of the negative electrode particles, etc. will all lead to a reduction in the gram capacity of the negative electrode material. In order to further provide a more targeted optimization guidance scheme for the structure of the negative electrode material, the present invention proposes a test method for the gram capacity loss of the negative electrode material of a failed lithium battery, which decomposes the reduction or loss of the gram capacity of the negative electrode material caused by the two influencing factors of the byproducts on the surface of the negative electrode particles and the crushing of the negative electrode particles, and provides an important role for the subsequent improvement direction to focus on improving the structural stability of the material itself or improving the stability of the SEI film (Solid Electrolyte Interface).

[0038] The present invention proposes a method for testing the gram capacity loss of a failed lithium battery negative electrode material. Figure 1 As shown, the following steps are included:

[0039] After discharging the failed lithium battery to an empty state, disassemble and remove the negative electrode sheet, clean the surface of the negative electrode sheet, dry it, and divide it into two parts;

[0040] The dressing on one side of the first negative electrode sheet is wiped off, and the negative electrode sheet is assembled into a button cell after being stamped by a mold, and the gram capacity of the failed negative electrode material is obtained through a small current charge and discharge test;

[0041] The dressing on one side of the second negative electrode sheet is scraped into powder, the powder is heated and calcined and then added to the acid solution, filtered and dried after reaction, the dried material powder is mixed with the conductive material to form a slurry, coated and cut and assembled into a button battery, and subjected to a small current charge and discharge test to obtain the gram capacity of the failed negative electrode material after cleaning;

[0042] Based on the gram capacity obtained from the test and the gram capacity of the non-failed lithium battery negative electrode material, the proportion of gram capacity loss of the negative electrode material caused by various influencing factors is calculated.

[0043] Furthermore, the above-mentioned factors that lead to the reduction or loss of the gram capacity of the negative electrode material of the failed lithium battery include byproducts on the surface of the negative electrode particles and the breakage of the negative electrode particles. Through the above-mentioned test method, the dressing powder scraped from the negative electrode sheet is heated and calcined to remove the organic byproducts on the surface of the negative electrode particles, and then the calcined powder is added to the acid solution and stirred, filtered and dried to remove the inorganic byproducts on the surface of the negative electrode. Through the above-mentioned method, the organic and inorganic byproducts on the surface of the negative electrode particles on the negative electrode sheet can be effectively removed, and then the gram capacity Q1 of the failed negative electrode material and the gram capacity Q2 of the failed negative electrode material after cleaning can be measured. Capacity Q2; on this basis, combined with the latest non-failed lithium battery negative electrode material gram capacity Q0 (which can be measured in advance), it can be calculated that the gram capacity loss of the failed negative electrode material is Q0-Q1, the gram capacity loss caused by by-products on the surface of the negative electrode material is Q2-Q1, and the gram capacity loss caused by the breakage of the negative electrode material is Q0-Q2. Furthermore, it is calculated that the proportion of gram capacity loss caused by by-products on the surface of the negative electrode material is (Q2-Q1) / (Q0-Q1), and the proportion of gram capacity loss caused by the breakage of the negative electrode material is (Q0-Q2) / (Q0-Q1).

[0044] Specifically, during the above test process, the failed lithium battery is discharged to an empty state, disassembled in a glove box and the negative electrode sheet is taken out for standby, or the negative electrode sheet is disassembled and taken out in a low-humidity disassembly room and packaged with an aluminum-plastic film, and then transferred to the glove box for standby; the disassembled negative electrode sheet is immersed in a carbonate solvent, such as 500mL of dimethyl carbonate reagent, in the glove box, and the lithium salt and electrolyte on the surface of the negative electrode sheet are cleaned by soaking for 4 hours, and then placed in a vacuum drying oven, baked at 80°C for 8 hours, and the dried negative electrode sheet is divided into two parts for standby.

[0045] For the two dried negative electrode sheets obtained, first, take one of the dried negative electrode sheets, use N,N-dimethylamide organic solvent to wipe off the dressing on one side of the negative electrode sheet, and use a mold to punch the negative electrode sheet after the dressing is wiped off into a small disc, and then assemble it into a button battery for lithium sheets, and use a small current of 0.05C to perform charge and discharge tests on the button battery, and the test voltage range is 0.05mV~2V. After testing, the gram capacity of the failed negative electrode material Q1 is obtained. Through this step, the gram capacity of the negative electrode material including particle surface byproducts and particle breakage can be obtained.

[0046] Secondly, take another dried negative electrode sheet, use a tool to scrape the surface dressing of the negative electrode sheet into powder, put the scraped powder into a horse furnace and heat it to 400℃ for roasting, keep it warm for 4 hours, and put it into the dryer after cooling to room temperature. Under normal circumstances, the organic byproducts on the surface of the negative electrode-alkyl lithium carbonate include: (CH2OCOOLi)2, CH3CH(OCOOLi)CH2OCOOLi, CH2OCOOLi, CH3CHOCOOLi, etc. These organic substances can be classified as alkyl lithium carbonate ROCOOLi, which decomposes into inorganic products such as CO2, Li2CO3, and Li2O when heated. In this way, the organic byproducts on the surface of the negative electrode particles-alkyl lithium carbonate can be effectively removed.

[0047] Then, add the powder in the dryer to a 1 mol L-1 dilute hydrochloric acid or dilute sulfuric acid solution and stir for 8 hours. Use ultrapure water to wash and filter the solid matter. Through this step, the inorganic byproducts on the surface of the negative electrode - lithium carbonate, lithium oxide, and lithium fluoride - can be removed. Usually, the inorganic byproducts on the surface of the negative electrode include: lithium carbonate Li2CO3, lithium oxide Li2O, lithium fluoride LiF, etc. These inorganic byproducts react with strong acids, such as hydrochloric acid and sulfuric acid, to generate water-soluble salts such as LiCl or Li2SO4, which can be removed by filtration. In this way, inorganic byproducts on the surface of negative electrode particles can be effectively removed.

[0048] After that, the cleaned solid material was placed in a vacuum drying oven and baked at 80°C for 12 hours to obtain material powder. The dried material powder was mixed with conductive carbon black, binder styrene-butadiene rubber SBR, and binder sodium carboxymethyl cellulose CMC to form a slurry, coated into a pole piece and cut into small discs, and then assembled with lithium sheets into a button battery. Among them, SBR and CMC are used to provide bonding. On this basis, the button battery was charged and discharged using a small current of 0.05C, and the test voltage range was 0.05mV~2V. The gram capacity of the failed negative electrode material after cleaning was obtained by testing Q2.

[0049] Furthermore, in the present invention, a charge and discharge test of a button cell is performed using a small current, including:

[0050] (1) 0.02-0.05C current discharge to 5mV;

[0051] (2) 0.02-0.05C current charging to 2V;

[0052] (3) Repeat steps (1) and (2) twice, and take the last charge capacity as the negative electrode gram capacity.

[0053] Through the above method, the proportion of gram capacity loss caused by by-products on the surface of negative electrode particles and the crushing of negative electrode materials in the gram capacity loss of negative electrode materials can be decomposed, so as to clarify the severity of the by-products on the surface of negative electrode materials and the crushing of negative electrode materials. According to the severity, the direction of improvement of subsequent failure problems can be determined, that is, the subsequent improvement is determined to improve the stability of the intrinsic structure of the negative electrode material or to improve the stability of the SEI film on the surface of the material.

[0054] Example 1

[0055] In this embodiment, the specific steps of the method for testing the gram capacity loss of the negative electrode material of a failed lithium battery are as follows:

[0056] First, take a lithium iron phosphate battery with a cycle failure, whose battery capacity is 73Ah, and the cycle conditions are: 25℃, 1C charging, 1C discharging, voltage range of 2.5~3.65V, charge and discharge standing time of 30min, and the capacity at the end of the cycle is 70% of the initial capacity. The lithium battery with cycle failure is discharged to an empty state, disassembled in the glove box and the negative electrode sheet is taken out for standby; in the glove box, 500mL of dimethyl carbonate reagent is used to soak the negative electrode sheet for 4 hours, and then the negative electrode sheet is transferred to a vacuum drying oven and baked at 80℃ for 8 hours. The dried negative electrode sheet is divided into two parts for standby.

[0057] Take the first dried negative electrode sheet, use N,N-dimethylacetamide solvent to wipe off the dressing on one side of the negative electrode sheet, punch the negative electrode sheet after the dressing is wiped off into small discs through a mold, assemble them into button batteries for lithium sheets, and use a small current of 0.05C to perform charge and discharge tests on the button batteries with a voltage range of 0.05mV to 2V to obtain the gram capacity Q1 of the failed negative electrode material.

[0058] Take another dried negative electrode sheet, use a ceramic scraper to gently scrape off the dressing on the electrode sheet, put the resulting powder into a crucible, and then put it into a muffle furnace, heat it to 400°C, keep it warm for 4 hours, cool it naturally to room temperature, and put it into a dryer for later use.

[0059] The calcined powder was placed in a beaker, 1 mol L-1 dilute hydrochloric acid was added and stirred for 8 hours. After stirring, the solution was filtered out to obtain a solid substance. The solid substance was washed with ultrapure water and then placed in a vacuum drying oven for drying at a temperature of 80°C for 12 hours.

[0060] Take 1g of the baked powder and mix it with conductive carbon black, SBR, and CMC in a mass ratio of 95:1.5:2:1.5, add an appropriate amount of water and stir to form a uniform slurry, use a vacuum coater to coat it on copper foil, and put it into a vacuum drying oven for drying, wherein the baking temperature is 95°C and the baking time is 8 hours, so as to obtain a pole piece; use a mold to punch it into small discs, assemble it into button batteries for lithium sheets, use a small current of 0.05C to perform charge and discharge tests on the button batteries, and the voltage range is 0.05mV~2V to obtain the gram capacity Q2 of the failed negative electrode material after cleaning the by-products on the surface of the particles.

[0061] Among them, the button battery is charged and discharged using a small current, as follows:

[0062] (1) 0.02-0.05C current discharge to 5mV;

[0063] (2) 0.02-0.05C current charging to 2V;

[0064] (3) Repeat steps (1) and (2) twice, and take the last charge capacity as the negative electrode gram capacity.

[0065] According to the gram capacity Q0 of the non-failed lithium battery negative electrode material obtained by pre-measurement, the gram capacity loss of the negative electrode material can be calculated to be Q0-Q1, the gram capacity loss caused by the by-products on the surface of the negative electrode material is Q2-Q1, and the gram capacity loss caused by the breakage of the negative electrode material is Q0-Q2. Then, the proportion of gram capacity loss caused by the by-products on the surface of the negative electrode material is calculated to be (Q2-Q1) / (Q0-Q1), and the proportion of gram capacity loss caused by the breakage of the negative electrode material is (Q0-Q2) / (Q0-Q1). Figure 2 Schematic diagram of the negative electrode charge and discharge curve of Example 1.

[0066] Comparative Example 1

[0067] Comparative Example 1 adopts the same implementation as Example 1, except that the lithium-ion battery used in Comparative Example 1 is a negative electrode sheet obtained by disassembling non-failed initial lithium batteries after capacity division from the same batch as Example 1. Figure 3 This is a schematic diagram of the negative electrode charge and discharge curve of comparative example 1.

[0068] Comparative Example 2

[0069] Comparative Example 2 adopts the same implementation as Example 1, except that: the lithium-ion battery used in Comparative Example 2 is another cycle-failed battery, and the battery cycle conditions are: 25°C, 2C charging, 2C discharging, voltage range of 2.5-3.65V, charge and discharge standing time of 30min, and the capacity at the end of the cycle is 70% of the initial capacity. Figure 4 This is a schematic diagram of the negative electrode charge and discharge curve of comparative example 2.

[0070] Comparative Example 3

[0071] Comparative Example 3 adopts the same implementation as Example 1, except that: the lithium-ion battery used in Comparative Example 3 is another cycle-failed battery, and the battery cycle conditions are: 45°C, 1C charging, 1C discharging, voltage range of 2.5-3.65V, charge and discharge standing time of 30min, and the capacity at the end of the cycle is 70% of the initial capacity. Figure 5 This is a schematic diagram of the negative electrode charge and discharge curve of comparative example 3.

[0072] Through the above experiments, the test results of the negative electrode material gram capacity of Example 1 and Comparative Examples 1, 2, and 3 are shown in Table 1 below.

[0073] Table 1 Comparison results of negative electrode material gram capacity mAh / g test

[0074]

[0075] As can be seen from Table 1 above, the gram capacity loss of the negative electrode material in the initial lithium battery in Comparative Example 1 is 3.4 mAh / g, about 0.96%, of which the gram capacity loss caused by the byproducts on the surface of the negative electrode material accounts for 64.71%, and the gram capacity loss caused by the crushing of the negative electrode material accounts for 35.29%, which shows that the initial state of the negative electrode gram capacity loss is very small, of which the loss caused by the byproducts on the surface of the negative electrode material accounts for slightly more than the loss caused by the crushing of the negative electrode material. The gram capacity loss of the negative electrode material in the cycle failure battery in Example 1 is 47.2 mAh / g, about 13.3%, of which the gram capacity loss caused by the byproducts on the surface of the negative electrode material accounts for 81.74%, which is much greater than the gram capacity loss caused by the crushing of the negative electrode material. This shows that the negative electrode material of the room temperature 1C cycle failure battery should focus on improving the stability of the SEI film on the surface of the material.

[0076] In Comparative Example 2, the gram capacity loss caused by the breakage of the negative electrode material accounts for 60.25%, which exceeds the gram capacity loss caused by the by-products on the negative electrode surface. This indicates that the 2C cycle at room temperature will aggravate the breakage of the negative electrode material compared with the 1C cycle at room temperature; in Comparative Example 3, the gram capacity loss caused by the by-products on the surface of the negative electrode material accounts for 84.86%, which is higher than the loss of by-products on the surface of the negative electrode material in Example 1. This indicates that the high-temperature cycle of 45°C will aggravate the generation of by-products on the surface of the negative electrode material compared with the normal temperature cycle.

[0077] Furthermore, considering the influencing factors of the byproducts on the surface of the negative electrode particles and the crushing of the negative electrode particles, based on the gram capacity obtained by the above measurement, the gram capacity loss ratio of the negative electrode material of the failed lithium battery caused by the byproducts on the surface of the negative electrode particles and the crushing of the negative electrode particles is compared. When the gram capacity loss ratio caused by the byproducts on the surface of the negative electrode particles is larger, the stability of the SEI film on the surface of the negative electrode material can be improved by improving the coating method of the surface of the negative electrode material and the electrolyte film-forming additives, so as to be suitable for high temperature and other usage scenarios; and when the gram capacity loss ratio caused by the crushing of the negative electrode particles is larger, the stability of the structure of the negative electrode material itself can be improved by increasing the graphitization degree of the negative electrode material. Through the above methods, the failure problem of lithium batteries can be effectively improved or the direction for improving the performance of negative electrode materials can be pointed out.

[0078] The above description is only a preferred embodiment of the present invention. Although the specific implementation mode of the present invention is described in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that on the basis of the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A method for testing the gram capacity loss of failed lithium battery negative electrode materials, characterized in that: include: After discharging the failed lithium battery to an empty state, disassemble and remove the negative electrode sheet, clean the surface of the negative electrode sheet, dry it, and divide it into two parts; The dressing on one side of the first negative electrode sheet is wiped off, and the negative electrode sheet is assembled into a button cell after being stamped by a mold, and the gram capacity of the failed negative electrode material is obtained through a small current charge and discharge test; The dressing on one side of the second negative electrode sheet is scraped into powder, the powder is heated and calcined and then added to the acid solution, filtered and dried after reaction, the dried material powder is mixed with the conductive material to form a slurry, coated and cut and assembled into a button battery, and subjected to a small current charge and discharge test to obtain the gram capacity of the failed negative electrode material after cleaning; Based on the gram capacity obtained from the test and the gram capacity of the non-failed lithium battery negative electrode material, the proportion of gram capacity loss of the negative electrode material caused by various influencing factors is calculated.

2. A method for testing the gram capacity loss of a failed lithium battery negative electrode material according to claim 1, characterized in that: Factors that lead to the loss of gram capacity of negative electrode materials include byproducts on the surface of negative electrode particles and the breakage of negative electrode particles; Based on the gram capacity Q1 of the failed negative electrode material and the gram capacity Q2 of the failed negative electrode material after cleaning, combined with the gram capacity Q0 of the non-failed lithium battery negative electrode material, it is calculated that the gram capacity loss of the failed negative electrode material is Q0-Q1, the gram capacity loss caused by by-products on the surface of the negative electrode material is Q2-Q1, and the gram capacity loss caused by breakage of the negative electrode material is Q0-Q2. Furthermore, it is calculated that the proportion of gram capacity loss caused by by-products on the surface of the negative electrode material is (Q2-Q1) / (Q0-Q1), and the proportion of gram capacity loss caused by breakage of the negative electrode material is (Q0-Q2) / (Q0-Q1).

3. A method for testing the gram capacity loss of a failed lithium battery negative electrode material as claimed in claim 2, characterized in that: The byproducts on the surface of the negative electrode particles include organic byproducts on the surface of the negative electrode particles and inorganic byproducts on the surface of the negative electrode particles. Among them, the organic byproducts on the surface of the negative electrode particles include alkyl lithium carbonate; the inorganic byproducts on the surface of the negative electrode include lithium carbonate, lithium oxide, and lithium fluoride.

4. A method for testing the gram capacity loss of a failed lithium battery negative electrode material as claimed in claim 2, characterized in that: According to the proportion of negative electrode material gram capacity loss caused by each influencing factor, the severity of different influencing factors is determined, and the performance of lithium battery negative electrode materials is improved according to the severity, including: Compare the percentage of gram capacity loss of failed lithium battery negative electrode materials caused by by-products on the surface of negative electrode particles and that caused by breakage of negative electrode particles. When the percentage of gram capacity loss caused by by-products on the surface of negative electrode particles is larger, the stability of the SEI film on the surface of the negative electrode material is improved; conversely, when the percentage of gram capacity loss caused by breakage of negative electrode particles is larger, the stability of the structure of the negative electrode material itself is improved.

5. A method for testing the gram capacity loss of a failed lithium battery negative electrode material as claimed in claim 1, characterized in that: Disassemble and take out the negative electrode sheet in a glove box or a low-humidity disassembly room, soak and clean the surface of the negative electrode sheet with 500 mL of dimethyl carbonate reagent for 4 hours, and dry it at 80°C in a vacuum drying oven for 8 hours.

6. A method for testing the gram capacity loss of a failed lithium battery negative electrode material according to claim 1, characterized in that: Use N,N-dimethylamide organic solvent to wipe off the dressing on one side of the first negative electrode sheet, and punch the negative electrode sheet after the dressing is wiped off into small discs through a mold, and then assemble it into a button battery of lithium sheets. Use a small current of 0.05C to perform charge and discharge tests on the button battery. The test voltage range is 0.05mV~2V. The gram capacity of the failed negative electrode material is Q1.

7. A method for testing the gram capacity loss of a failed lithium battery negative electrode material according to claim 1, characterized in that: The scraped powder was placed in a furnace and heated to 400°C for calcination, kept at this temperature for 4 hours, cooled to room temperature and then placed in a dryer; The powder in the dryer was added to 1 mol L-1 dilute hydrochloric acid or dilute sulfuric acid solution and stirred for 8 h. The solid matter obtained by filtration was washed with ultrapure water and the washed solid matter was placed in a vacuum drying oven and baked at 80 °C for 12 h to obtain material powder.

8. A method for testing the gram capacity loss of a failed lithium battery negative electrode material as claimed in claim 1, characterized in that: The dried material powder is mixed with conductive material to form a slurry, coated into pole pieces and cut into small discs, and then assembled with lithium sheets into button batteries. The button batteries are charged and discharged using a small current of 0.05C. The test voltage range is 0.05mV to 2V. The gram capacity of the failed negative electrode material after cleaning is obtained by testing Q2.

9. A method for testing the gram capacity loss of a failed lithium battery negative electrode material as claimed in claim 8, characterized in that: The conductive material includes conductive carbon black, SBR, and CMC; Take 1 g of the dried material powder, mix it with conductive carbon black, SBR and CMC in a mass ratio of 95:1.5:2:1.5, and stir to obtain a slurry.

10. A method for testing the gram capacity loss of a failed lithium battery negative electrode material according to claim 8, characterized in that: The slurry was coated on the copper foil by using a vacuum coater, and then placed in a vacuum drying oven for drying to obtain a machine sheet; wherein, the baking temperature was 95° C. and the baking time was 8 h.